Basic schooling in Brazil: advances, continuance, and contrasts between rural e urban populations - Damiana de Matos Costa França (Universidade Federal do Norte do Tocantins, 2021)
The text presents, through statistical data, a reflection on the situation of basic schooling of the population residing in the countryside, vis-à-vis the population residing in the urban area, in order to understand advances and permanence of the conditions of the educational offer and its effects in the distance and in the approximation of the guarantee of social justice and the right to schooling. The methodological process involved content analysis and the construction of quantitative data provided by the Brazilian Institute of Geography and Statistics (IBGE), the National Institute of Educational Studies and Research Anísio Teixeira (INEP) and the Institute for Applied Economic Research (IPEA). For the study, these categories were selected: number of countryside schools, years of study and schooling access by location (rural/urban). The data express an inequality situation in the schooling indicators of rural areas and the Brazilian North and Northeast regions. Despite the advances, the inequalities in the Brazilian educational system are significant and strongly evidenced in the contrast between rural and urban areas. The persistence of unfavorable situations increases the inequality condition of the rural population.